2012
DOI: 10.1111/j.1574-6941.2012.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of mycovirus-like double-stranded RNAs in the white root rot fungus,Rosellinia necatrix, in an apple orchard

Abstract: In general, mycoviruses are transmitted through hyphal anastomosis between vegetatively compatible strains of the same fungi, and their entire intracellular life cycle within host fungi limits transmission to separate species and even to incompatible strains belonging to the same species. Based on field observations of the white root rot fungus, Rosellinia necatrix, we found two interesting phenomena concerning mycovirus epidemiology. Specifically, apple trees in an orchard were inoculated with one or two R. n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 45 publications
(76 reference statements)
7
42
0
Order By: Relevance
“…Milgroom and Cortesi concluded that the success of using hypoviruses to control chestnut blight at the population level depended on the natural spread of viruses, and they thought that the application of hypovirulenceassociated mycoviruses for biological control of other plant-pathogenic fungi was likely to meet the same constraints as those for chestnut blight (40). Our findings and previous studies on potential mycovirus transmission vectors (14)(15)(16)(17) suggest that vectors for mycoviruses are likely to exist in nature, and other mycophagous insects may function as mycovirus transmission vectors, as many fungi could release volatiles to attract insects (41). Thus, L. ingenua is not likely to be the only transmission vector for mycoviruses.…”
Section: Discussionsupporting
confidence: 70%
“…Milgroom and Cortesi concluded that the success of using hypoviruses to control chestnut blight at the population level depended on the natural spread of viruses, and they thought that the application of hypovirulenceassociated mycoviruses for biological control of other plant-pathogenic fungi was likely to meet the same constraints as those for chestnut blight (40). Our findings and previous studies on potential mycovirus transmission vectors (14)(15)(16)(17) suggest that vectors for mycoviruses are likely to exist in nature, and other mycophagous insects may function as mycovirus transmission vectors, as many fungi could release volatiles to attract insects (41). Thus, L. ingenua is not likely to be the only transmission vector for mycoviruses.…”
Section: Discussionsupporting
confidence: 70%
“…This distribution resembles the uneven distribution of viruses within clones of the pathogenic root rot fungi Helicobasidium mompa (Ikeda et al, 2005) and Rosellinia necatrix (Yaegashi et al, 2013) and the ascomycetous pathogen C. parasitica (Shain and Miller, 1992;Hoegger et al, 2003). We have shown that the partitivirus HetPV4 (formerly HetRV4) was transmitted via hyphal contact from an introduced strain of H. parviporum into native strains inhabiting Norway spruce stumps (Vainio et al, 2013a).…”
Section: Discussionmentioning
confidence: 95%
“…W1029 is believed to be one of the subisolates that has naturally acquired dsRNA segments of RnVV1 and a partitivirus termed Rosellinia necatrix partitivirus 3-W1029 (RnPV3-W1029) in the soil. The genomic segments of these viruses were referred to as S1 and S2 by Yaegashi et al (36). The genotype and MCG (mycelial compatibility group) of W1029 were confirmed previously to be identical to the parental W563 (MCG139).…”
Section: Methodsmentioning
confidence: 82%
“…Rosellinia necatrix strain W1029 was reisolated in 2009 from an experimental orchard of apple trees (Nagano Fruit Tree Experiment Station) at Suzaka, Nagano Prefecture, Japan, where virusfree W563 had been buried in 2007 (36). W1029 is believed to be one of the subisolates that has naturally acquired dsRNA segments of RnVV1 and a partitivirus termed Rosellinia necatrix partitivirus 3-W1029 (RnPV3-W1029) in the soil.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation